HUBUNGAN WAKTU TUNGGU PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN DI INSTALASI GAWAT DARURAT RUMAH SAKIT X - Riswahyuni Widhawati (STIKes IMC Bintaro, 2021)
Background: Waiting for a long time causes patient dissatisfaction. By knowing the characteristics of the respondents which include gender, age level, occupation, education level, old / new visits, and the use of health insurance that utilizes health services at the X Hospital Emergency Room. Objective: To determine the level of patient satisfaction using health services, average waiting times, the relationship between service waiting times and patient satisfaction levels. Methods: This study used an observational analytic method with a cross-sectional study approach (cross-sectional study). The research instrument in the form of a questionnaire, the number of respondents in this study were 103 people. The statistical test used was the chi square test. Results: The level of satisfaction in the category is quite satisfied, based on the five dimensions of service quality obtained in the dimensions of tangible, responsiveness, reliability, assurance, empathy. The average waiting time at Igd Hospital X in 2020 is 42.18 minutes and most of the time categories are fast (<60 minutes). The chi square test shows the p value of 0.001 <α value, which means that Ha is accepted and Ho is rejected, so it can be concluded that there is a significant relationship between waiting time and the level of patient satisfaction in the ER at Hospital X in 2020. Conclusions and suggestions: The hypothesis proposed is accepted (there is a relationship between waiting time and patient satisfaction). Therefore, the hospital should provide comfortable and adequate facilities in the waiting room to avoid patients feeling bored. It is recommended for further researchers to make direct observations and conduct long-term research to determine how much influence waiting time has on patient satisfaction.